Coordination Improvement in Inventory Management for Electricity Distribution Materials - Rahmadani, Diajeng Anjarsari; Arvitrida, Niniet Indah (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2025)
Electricity is a fundamental necessity. Its demand is characterized by fluctuation and broad geographic dispersion, requiring distribution units of electricity companies to be prepared to serve customer needs across all areas. The growing demand also necessitates expanding distribution networks. Establishing new connections for customers requires various materials, among which power cables are among the most crucial. However, procuring and managing these materials involves multiple stakeholders, leading to inventory management complexities. This study aims to enhance coordination in power cable inventory management by analyzing how improved coordination influences procurement costs through simulation. This study utilizes system dynamics method to understand the system of inventory management and the interactions among its elements. The existing inventory management was simulated and compared with a coordination policy scenario. The coordination policy yields better cost outcomes by managing internal coordination between two divisions, efficiently changing the use of budget and cost related to inventory. These insights can guide company management to apply the policy and enhance inventory performance for primary electricity distribution materials.